Análisis Jurisprudencial del Fallo de Triple Reiteración 06-2016 en relación a las garantías laborales de la mujer gestante frente a principios y garantías constitucionales - Briceño Yunga, María José (2024)
The main objective of this graduation project is to legally analyze the ineffective dismissal concerning pregnant women in Ecuadorian legislation. A qualitative approach, historicallogical method, and analytical-synthetic method were used for an analysis of ineffective dismissal, detailing the reformed norm according to the Constitution of the Republic of Ecuador, the Labor Code, the Organic Law for Labor Justice and Recognition of Work in the Home. This includes an examination of rights within the national and international framework through the application of documentary analysis technique. The legal evidence, primarily and of relevance, developed in the Judgment of Triple Reiteration 06-2016 of the National Court, demonstrates the violation of labor and constitutional rights of pregnant women and the need to strengthen the legal concept of ineffective dismissal. This is due to the inadequacy of compensation for their needs. The Organic Law for Labor Justice and Recognition of Work in the Home (2015) reformed the Labor Code and introduced the concept of ineffective dismissal. Its purpose is to protect pregnant women from untimely dismissal, guarantee the right of pregnant women to return to their work, and if they choose not to return, considerations will be made according to the law. If the employer does not want their reinstatement, they may be penalized according to the Comprehensive Organic Penal Code. The normative scope of timely notification of pregnancy status is also established.